PARENTS AND CHILDREN TOGETHER (PACT) FOR A HEALTHY MIND - Shah , Syed Mahboob (Journal of Pakistan Psychiatric Society, 2023)
Non-communicable diseases (NCDs) and poor mental health are the leading cause of premature mortality and morbidity globally. According to global estimates 70% risk factors for NCDs develop during childhood and adolescence. Suicide is leading cause of death among adolescents. Both parents and children need to work together for a healthy future.